The monk and the white shaman, competeitive discourses and conspiracy theories around the reinterpreted cult of Blessed Eusebius - Povedák István; Özséb (2014)
In the past two decades a Hungarian neo-mythology appeared and is being shaped with amazing speed. It comprises partly neopagan and partly Christian, neo-nationalist elements and one of its prominent segments is the re-interpreted cult of Blessed Eusebius (c. 1200-1270). In this invented mythology, Blessed Eusebius and the Pauline Order he established becomes a white shaman and the guardian of the ancient Hungarian religion. The image of the Paulines in the invented mythology gained considerable popularity, mainly in non-Catholic circles. The main aim of the study is to show the origin of the mythology, its ele-ments and the characteristics of the changing cult.
Keywords: Bölcsészettudományok; Történettudomány és régészet; Filozófia, etika és vallástudományok